PROYECTO DE FACTIBILIDAD PARA LA CREACION DE UN BAR-KARAOKE, EN LA CIUDAD DE CATAMAYO - Sánchez Quizhpe, Janina Alexandra (2016)
This project aims to determine the feasibility of creating a karaoke bar in the city of Catamayo, and thus generate jobs, contributing to the improvement of the socio-economic conditions catamayo canton. In the market study proceeded to the collection of information by applying surveys of 385 people aged 18 to 65 years of the city of Catamayo, only to be tabulated, processed and interpreted so as to present the results and thus determine the unmet demand for 96,407 people in the year of study and market strategies for service. In the technical study the ability to install that will be 8,320 people per year and the percentage to be used for the service, which will leave 80% of the 6,656 people promoting capacity was determined. It also is cost process descriptions, flowcharts for the service process. Thus the quality of service is ensured. The location of the company will be the Barrio la Vega. In the organizational study of the company is based on the different rules and regulations in order to facilitate a smooth operation, describes the elements necessary for the administration and the business structure, hierarchical levels, minuta, organizational and operating manuals. 5 For the implementation of this project requires a capital of $ 22.653,22 the same as the 56% with equity and 44% external source, credit it held in the National Financial Corporation, with interests of 10% will be financed. The company worked at 80% of its installed capacity with what the service will be provided to 6,656 people, generating revenues of 67,729.51. The cost of the service is $ 9.25 with 10% profit being its retail price of $ 10.18 per public person is a price that people can spend on the Bar. When performing the financial analysis is the net present value of 20,871.08, the Capital Recovery Period will be 2 years 6 months and 7 days; Benefit Cost Ratio is 1.18; the internal rate of return is 36.90; when making an increase in costs of up to 3.14% the project is not sensitive; and, when performing a decrease in revenues to 2.64% of the project is not sensitive; It allows for the project if it is feasible for implementation of the project.